2016
DOI: 10.3329/cmoshmcj.v15i1.28761
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Computer Related Musculoskeletal Disorders Among Bankers of Dhaka City

Abstract: Introduction: Bangladesh is a developing country and the industrialization process is also getting momentum. Due to rapid industrialization and mechanization, use every day more people are coming in contact with the information technology, consequently computer use which may enhance sufferings of people by causing musculoskeletal disorders.Objective: to find out among bankers (a) the prevalence of musculoskeletal disorder and (b) the association between musculoskeletal pain and computer use.Methods: This descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 8 publications
2
25
1
Order By: Relevance
“…However, working hour per day was only associated with musculoskeletal pains. Similar studies conducted among office workers found an association between job duration and working hours per day with musculoskeletal pains [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 60%
“…However, working hour per day was only associated with musculoskeletal pains. Similar studies conducted among office workers found an association between job duration and working hours per day with musculoskeletal pains [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 60%
“…Doing physical exercises 3 times a week for 20 minutes can be reduce musculoskeletal pain in different parts of the body like shoulder, neck and lumbar spine. 1 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Bankers are expected to perform at computer workstations for long periods of time. 1 , 3 They work for 8 hours per day, and 6 days per week. Bankers use computers for data collection, processing, and programing in the banking industry.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 In this study, 68.3% of residents had poor awareness and only This type of posture also puts a strain on the lower back and knees. 27, 28 Posture correction is an important factor to reduce low back pain. 29 69.2% (n=157) didn't have a chair which has a curve that fits the lordotic curve of the lower back, so by using these type of chairs residents didn't get upper and lower back support.…”
Section: Discussionmentioning
confidence: 99%